ANALISIS BREAK EVEN POINT SEBAGAI ALAT PERENCANAAN LABA PADA PT. HADJI KALLA (KALLA TOYOTA) CABANG POSO - Ilyas Martunus (Ekomen, 2014)
This study was conducted at PT . Hadji Kalla ( Kalla Toyota ) Branch Poso in order to determine the volume of sales ( units and dollars ) in order to Break Even Point ( BEP ) at PT . HadjiKalla ( Kalla Toyota ) Branch Poso and to determine the volume of sales at the level of the expected profit . The data used in this research is secondary data, the data obtained from the documents that exist on the PT . Hadji Kalla ( Kalla Toyota ) Branch Poso and other supporting literature . And then analyzed quantitatively.The results showed bahwaPT . Hadji Kalla ( Kalla Toyota ) Branch Poso in 2013. BEP BEP perunitmencapai 48 units and dollars on position Rp . 10.472264 billion. Based on the analysis that the PT . Hadji Kalla ( Kalla Toyota ) Branch Poso can plan sales in 2014 with expected Rp . 5,000,000,000 , - then the company should sell the product as much as 138 unit and on position Rp sales . 30.472264 billion.Keyword : Break Even Point ( BEP ), volume of sales, expected profit